Fuelling hydrogen futures? A trust-based model of social acceptance - Gordon, Joel A.; Balta-Ozkan, Nazmiye; Haq, Anwar U. l.; Nabavi, Seyed Ali (Royal Society of Chemistry (RSC), 2025)
Public trust plays a fundamental role in shaping national energy policies in democratic countries, as exemplified by nuclear phase-out in Germany following the Fukushima accident. While trust dynamics have been explored in different contexts of the energy transition, few studies have attempted to quantify the influence of public trust in shaping social acceptance and adoption potential. Moreover, the interaction between public trust and perceived community benefits remains underexplored in the literature, despite the relevance of each factor to facilitating social acceptance and technology uptake. In response, this quantitative analysis closes a parallel research gap by examining the antecedents of public trust and perceived community benefits in the context of deploying hydrogen heating and cooking appliances across parts of the UK housing stock. Drawing on results from a nationally representative online survey (N = 1845), the study advances insights on the consumer perspective of transitioning to ‘hydrogen homes’, which emerged as a topical and controversial aspect of UK energy policy in recent years. Partial least squares structural equation modelling and necessary condition analysis are undertaken to assess the predictive capabilities of a trust-based model, which incorporates aspects of institutional, organisational, interpersonal, epistemic, and social trust. Regarding sufficiency-based logic, social trust is the most influential predictor of public trust, whereas trust in product and service quality corresponds to the most important necessary condition for enabling public trust. Nevertheless, trust in the government, energy sector, and entities involved in research & development are needed to facilitate and strengthen public trust. Overall, this study enriches scholarly understanding of how public trust may shape prospects for trialling novel low-carbon technologies, highlights the need for segment-specific consumer engagement, and advances scholarly understanding of the innovation-decision process in the context of net-zero pathways. As policymakers approach critical decisions on the portfolio of technologies needed to support residential decarbonisation, public trust will prove fundamental to fuelling hydrogen-based energy futures.
Keywords: 34 Chemical Sciences; 40 Engineering; 3406 Physical chemistry; 4004 Chemical engineering; 4008 Electrical engineering